Efficacy of acupuncture on lower limb motor dysfunction following stroke: A systematic review and meta-analysis of randomized controlled trials - Peng Chen; Xing Jin; Debiao Yu; Xiaoting Chen; Yaoyu Lin; Fuchun Wu; Bin Shao (PLoS ONE, 2025)
Background Acupuncture is widely used for Lower Limb Motor Dysfunction Following Stroke (LLMD) in China, though its effectiveness remains unclear. This meta-analysis aims to evaluate the effectiveness of acupuncture for LLMD. Methods We searched eight databases, including PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang, VIP, and CBM, up to December 2023. Randomized controlled trials on acupuncture therapy for LLMD after stroke were included in this study. Outcome measures included motor function, balance function, walking ability, and daily living activities. Two researchers conducted independent literature screening, data extraction, and quality assessment in accordance with Cochrane Collaboration network’s standards. Review Manager 5.3 and Stata 17.0 were used in data analysis. Results were presented as mean difference (MD) or standardized mean difference (SMD) with 95% confidence interval (95% CI). Results Twelve studies involving 1318 patients, most of which showed low or unclear risk of bias, were included in this review. Meta-analysis results indicate that compared with conventional treatment, acupuncture intervention can improve scores in Fugl–Meyer Assessment for lower scale (SMD = -0.48, 95% CI [-0.92, –0.04], Z = 2.16, P = .03), Berg Balance Scale (SMD = -0.86, 95%CI [-1.65, –0.07], Z = 2.14, P = .03), Functional Ambulation Category scale (SMD = -0.74, 95%CI [-2.33, 0.84], Z = 0.92, P = .36), and Modified Barthel Index Scale (SMD = 0.27, 95%CI [-0.30, 0.84], Z = 0.94, P = .35). Conclusion The results of this study suggest that acupuncture combined rehabilitation training may be more effective than conventional rehabilitation alone in improving LLMD, balance function, walking ability, and daily living activities after stroke. Despite limitations due to the low quality of the included studies and methodological constraints, acupuncture combined with rehabilitation training may serve as an effective approach for the treatment of LLMD poststroke.